The study on plant hormones and spent mushroom compost on the growth of ficus carica - Siti Hamidah Radiyah, Shiekh Mahmud (2021)
Ficus carica (F. carica) or fig tree from mulberry family (Moraceae) known as „buah tin‟ among Malaysians highly demand from pharmaceutical area for its nutritional value. The objective of this research is to determine the optimize sterilization technique and concentrations of plant growth regulator and SMC use. In vitro culture of fig plant under controlled environment was introduced in fulfilling the demand for mass propagation of high quality planting material and Pleurotus ostreatus spent mushroom compost (SMC) which is a waste substrate was used as an alternative nutrient supplier. Upon in vitro culture of fig plant, phytochemical test and Fourier transform infrared spectrophotometer (FTIR) analysis were also conducted to highlight the important functional groups of secondary metabolites related to this plant that can give benefits to medicinal area. The first part is production of aseptic plantlets through sterilization process for in vitro fig‟s culture. The best sterilization technique was treatment 3 (T3) of 70% ethanol for 10 minutes, 30% clorox added with two drops of Tween 20 for 10 minutes and 0.01% silver acetate for 5 minutes. The second part is the shoots and root inductions conducted in different types of media that supplemented with plant growth regulator, SMC and combination of PGR and SMC. The highest shoot proliferations in presence of plant hormone were achieved at 15 µM Kinetin. For roots proliferation, the highest number of root was found in 30 µM IAA cultures. For media supplemented with SMC, the highest number of shoots was obtained in 10% SMC media. However, new roots were failed to grow in media supplemented with SMC only. PGR (15 µM Kinetin and 30 µM IAA) and SMC (10%) were combine with highest proliferations of shoots in combination media were 15 µM Kinetin with 10% SMC media with maximum number of shoot proliferation achieved (3.00 ± 1.27) and length of shoots (0.23 cm ± 0.08). The maximum number of root (0.50 ± 0.84) and length of root (0.10 ± 0.16) was achieved in 30 µM IAA + 10% SMC culture. The phytochemical test conducted for extracts of F.carica leaves indicates the presence of functional group of secondary metabolites such as amine, aromatic, nitrile, carbonyl, alkene, nitro and alkyl halide which is align with FTIR result. In conclusion, optimal use of plant growth regulator and SMC enables the promoting of new shoots and roots for fig nodal culture. SMC can be innovate from waste material to provide carbon and nutrient and minimizes the usage of plant hormone in micropropagation of fig plant.